Model Lanskap Kampung Adat Wologai Berbasis Budaya Suku Lio - Ignasia Germania M. Rada; Andi Gunawan; Akhmad Arifin Hadi (Jurnal Lanskap Indonesia, 2026)
Wologai Traditional Village in Ende Regency, East Nusa Tenggara, represents a living cultural landscape of the Lio indigenous people, reflecting a regenerative relationship between humans, nature, and ancestral spirits. The village’s spatial structure is oriented around local cosmology and deeply embedded with strong social and spiritual values. This study aims to analyze the Wologai traditional settlement model based on local cultural wisdom. The methodology includes literature review to identify natural and man-made landscape elements, interviews with Mosalaki (traditional leaders) and village heads regarding socio-cultural aspects, and direct observation of the traditional spatial structure. The findings show that the Mountain, Keda, and Kanga function as cosmological centers that shape the spatial organization and social relations of the community. The clustered and hierarchical settlement pattern reflects the integration of humans, nature, and ancestors, and serves as a symbol of spiritual and social sustainability. This study recommends the preservation of traditional spatial patterns and the strengthening of the roles of village governments and customary communities. The findings are expected to serve as a reference for the development and preservation of Wologai Traditional Village as a living and dynamic cultural heritage.